Collaborative cardiovascular management of patients with chronic myeloid leukemia on tyrosine kinase inhibitors. (June 2020) - Kondapalli, Lavanya; Worth, Sarah; Hawi, Riem; Vachhani, Pankit; Arora, Garima; Bhatia, Ravi; Lenneman, Carrie G
Tyrosine kinase inhibitors (TKIs) of the BCR-ABL fusion protein have dramatically changed the mortality of chronic myeloid leukemia (CML) but they carry a risk of serious vascular morbidity. While TKIs do not cure CML, daily oral administration of a TKI can control CML and TKIs are chronic medications. Interestingly, vascular complications can occur at any time a patient is on a TKI. Therefore, it is imperative that all care team members and patients are aware of and watching for possible vascular complications. In the following review, a case of arterial thrombosis secondary to the TKI ponatinib is presented as well as a discussion of thrombotic and vascular adverse events reported with TKIs. TKIs are metabolized through the cytochrome P450 system and important drug interactions to consider are reviewed. Finally, we present a multidisciplinary approach to the management of patients with CML on TKIs.